Peningkatan Keterampilan Berbicara Melalui Metode Diskusi Kelompok Pada Siswa Kelas XI SMAN 2 Bantaeng - Eka Purnamasari; Sitti Rahmawati; Ihramsari Akidah (Departement of Mathematics Education, 2023)
This study aims to describe the application of the group discussion method in improving the speaking skills of class XI students of SMAN 2 Bantaeng. The type of research used is Classroom Action Research (PTK) which is carried out in cycles. Each cycle has four stages, namely, the stages of planning, implementation, observation and reflection. The subjects in the study were students of class XI IPS 1 at SMAN 2 Bantaeng, totaling 28 students. The results of research on students' ability to speak using the group discussion method in class XI students of SMA Negeri 2 Bantaeng showed an increase in learning outcomes in each cycle and qualifications achieved in cycle II by achieving the provisions of the indicator of success that must be achieved, namely 75% of students who get a Minimum Completeness Criteria (KKM) score of 78. The learning outcomes in cycle I are with a percentage result of 25% or with an average result of 60.46 different in cycle II those who experienced changes were more effective, namely with a percentage result of 79% or with an average result of 80.42 in cycle II students were more enthusiastic in participating in the learning.